Arthroscopic Simulation: The Future of Surgical Training. Issue 3 (March 2021) - Lakhani, Saad; Selim, Omar A.; Saeed, Muhammad Zahid
Abstract : Background: Arthroscopic simulation has rapidly evolved recently with the introduction of higher-fidelity simulation models, such as virtual reality simulators, which provide trainees an environment to practice skills without causing undue harm to patients. Simulation training also offers a uniform approach to learn surgical skills with immediate feedback. The aim of this article is to review the recent research investigating the use of arthroscopy simulators in training and the teaching of surgical skills. Methods: A systematic review of the Embase, MEDLINE, and Cochrane Library databases for English-language articles published before December 2019 was conducted. The search terms included arthroscopy or arthroscopic in combination with simulation or simulator. Results: We identified a total of 44 relevant studies involving benchtop or virtually simulated ankle, knee, shoulder, and hip arthroscopy environments. The majority of these studies demonstrated construct and transfer validity; considerably fewer studies demonstrated content and face validity. Conclusions: Our review indicates that there is a considerable evidence base regarding the use of arthroscopy simulators for training purposes. Further work should focus on the development of a more uniform simulator training course that can be compared with current intraoperative training in large-scale trials with long-term follow-up at tertiary centers.